Analisis Thermal Terhadap Putaran Fan (Rpm) Pada Mesin Pengering Kakao Kapasitas 2 Kg Menggunakan Panel Surya - Ferby Dial Sugianto Sinaga; Jhon Sufriadi Purba; Winfrontstein Naibaho (Jurnal Teknik Mesin, 2022)
Cocoa (Theobroma cacao L) is a plant originating from South America. Indonesia has two types of cocoa grown, namely noble cocoa (edel) and bulk cocoa, for better quality cocoa is bulk cocoa. The part of cocoa that is used is the seeds that have been dried and then processed into cocoa powder. Cocoa beans that have been harvested are fermented so that they can be sold by cocoa through testing can be seen using tables and graphs in the development of the test every hour. The heat transfer in this test is conduction and convection. The results of the first test using a variation of 6 heater elements obtained data from 2000gram wet cocoa to 1100gram dry cocoa. This test got the highest temperature of 39.50C for 11 hours. The second test of variations with 6 heater elements and an additional fan got the highest temperature of 41.50C for 10 hours with cocoa after testing 1150gram. The second test found cocoa with the best level of AA because there were 84 dry beans in 100gram, the color was dry brown and the drying time was faster than the traditional method, such as farmers usually requiring 5 to 7 days of drying.